Long-Term Cost-Effectiveness and Return-on-Investment of a Mindfulness-Based Worksite Intervention: Results of a Randomized Controlled Trial. Issue 6 (June 2016) - van Dongen, Johanna M.; van Berkel, Jantien; Boot, Cécile R.L.; Bosmans, Judith E.; Proper, Karin I.; Bongers, Paulien M.; van der Beek, Allard J.; van Tulder, Maurits W.; van Wier, Marieke F.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: The aim of this study was to conduct a cost-effectiveness and return-on-investment analysis comparing a mindfulness-based worksite intervention to usual practice. Methods: Two hundred fifty-seven governmental research institute employees were randomized to the intervention or control group. Intervention group participants received an eight-week mindfulness training, e-coaching, and supporting elements. Outcomes included work engagement, general vitality, job satisfaction, work ability, and costs. Cost-effectiveness analyses were conducted from the societal and employer's perspective, and a return-on-investment analysis from the employer's perspective. Results: After 12 months, a significant but not clinically relevant adverse effect on work engagement was found (−0.19; 95% confidence interval: −0.38 to −0.01). There were no significant differences in job satisfaction, general vitality, work ability, and total costs. Probabilities of cost-effectiveness were low (≤0.25) and the intervention did not have a positive financial return to the employer. Conclusion: The intervention was neither cost-saving nor cost-effective. Poor e-coaching compliance might partly explain this result.